2015
DOI: 10.21273/hortsci.50.10.1453
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Leaf Nutrient Concentration of Northern Highbush Blueberry Cultivars Grown in Conventional and Organic Production Systems

Abstract: Northern highbush blueberry (Vaccinium corymbosum L.) cultivars were evaluated for leaf and fruit nutrient concentration at two production sites in 2013-14. The treatments included cultivar (Duke, Bluecrop, Draper, Legacy, Liberty, and Aurora), site [''conventional'' (conventionally managed, grower-collaborator site) and ''organic'' (certified organic research site)], and amendment-mulch [at the organic site only; ''organic mulch'' (included preplant amendment and a surface mulch of yard debris compost and saw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
46
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 18 publications
8
46
3
Order By: Relevance
“…Consequently, the plants were slightly chlorotic that spring but recovered quickly once fertigation was initiated and one or two applications of urea were applied. Strik and Vance (2015) also reported low leaf P in various cultivars of northern highbush blueberry in western Oregon, but the concentrations measured in the present study in year 2 were below those reported previously for 'Duke' (Larco et al, 2013b;Strik and Vance, 2015). Phosphorus uptake is sometimes limited in fertigated plants because of the smaller size of the root system (Bryla, 2011).…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…Consequently, the plants were slightly chlorotic that spring but recovered quickly once fertigation was initiated and one or two applications of urea were applied. Strik and Vance (2015) also reported low leaf P in various cultivars of northern highbush blueberry in western Oregon, but the concentrations measured in the present study in year 2 were below those reported previously for 'Duke' (Larco et al, 2013b;Strik and Vance, 2015). Phosphorus uptake is sometimes limited in fertigated plants because of the smaller size of the root system (Bryla, 2011).…”
Section: Resultscontrasting
confidence: 65%
“…Most of the leaf nutrient concentrations were within the recommended range for northern highbush blueberry in Oregon; however, leaf Mg, S, and Mn were above and leaf Cu was below recommendations in year 1, while leaf Fe was above and leaf N and P were below recommendations in year 2 . Low leaf Cu in not unusual when Cu-containing fungicides are omitted from the pest management program (Strik and Vance, 2015). Leaf Fe may have been high in year 2 because of dust on the leaves (not washed before analysis).…”
Section: Resultsmentioning
confidence: 99%
“…The amendment-mulch treatments led to differences in soil pH, OM, and particularly levels of soil Ca, Mg, and K (Table 3). Despite these differences in soil properties, Strik and Vance (2015) noted no effect of amendment-mulch on leaf nutrient concentrations in this same research planting other than for manganese (Mn) and aluminum (Al) whose availability is decreased at high soil pH. Therefore, although compost supplied a high rate of total N (Table 1), and an estimated 25 kg · ha -1 N released per year of the study, it apparently supplied low amounts of plant-available N, or the added N was not required by the plants.…”
Section: Resultsmentioning
confidence: 99%
“…Larco et al (2013bLarco et al ( , 2014 also found that yard-debris compost provided little to no plant-available N when used as part of a mulching program in organic blueberry production. In our study, the nutrients applied via fertilization (Table 2) were thus considered sufficient for plant growth based on plant tissue analysis (Strik and Vance, 2015) and observed growth. The high pH in the organic amendment-mulch treatment, however, likely reduced plant growth and yield in some cultivars (see below).…”
Section: Resultsmentioning
confidence: 99%
“…These observations, combined with the low transpiration conditions preceding onset of drop, indicated similarities to other Ca deficiencies such as blossom end rot in tomato (Solanum lycopersicum L.) and bitter pit in apples (Malus pumila Miller) [5][6][7]. In Oregon, relative to other cultivars, 'Draper' showed low fruit Ca and high leaf Ca [8].…”
Section: Introductionmentioning
confidence: 74%